Modern Notation of Business Models: A Visual Trend - Tatiana Gavrilova; Artem Alsufyev; Anna-Sophia Yanson (Foresight and STI Governance)
Information overflow and dynamic market changes encourage managers to search for a relevant and eloquent model to describe their business. This paper provides a new framework for visualizing business models, guided by well-shaped visualization based on a mind mapping technique introduced by Tony Buzan. The authors’ approach amplifies Alexander Ostervalder’s ideas on the new level of abstraction and well-structured description of business models. It also seeks to simplify the Osterwalder model. As a result, the new form of visualization enhances perception, increases the quality of business communication and decreases cognitive pressure.